Seasonal variations in antibody response to a Plasmodium falciparum recombinant circumsporozoite antigen in two villages in South Western Nigeria (2006)
An Enzyme Linked Immunosorbent Assay (ELISA), employing a recombinant peptide capture antigen (R32tet32) was used to detect antibodies against the circumsporozoite protein (CSP) of the malaria parasite, Plasmodium falciparum in 169 serum samples from 16 subjects from two villages, Afefu (FA) and Tobalogbo (TB), in Igbo-Ora Community of Oyo State, over a period of 12 months. The maximum and mean Ab response for FA was higher than for TB samples (0.511 AU±0.170, 0.124±0.045U and 0.250±0.070 AU, 0.090±0.019AU respectively), with the mean Ab being significantly different (t=2.313; P>0.05). Despite both villages (FA and TB) falling within the same rainfall data zone, the Ab response profile for FA showed a positive (seasonal) relationship with rainfall (r=+0.31, P>0.05) while that of TB was negatively correlated (r=-0.32; P>0.05). Habits and the environment could be prime contributing factors alongside the less controllable immunogenetic factors. Data obtained here would serve as baseline and we suggest other expanded sample size studies to include data on temperature and other climatic factors to help establish sub-populations at risk and better empower malariologists in planning and execution of control programmes.